2017
DOI: 10.1111/jac.12250
|View full text |Cite
|
Sign up to set email alerts
|

Maize harvest index and water use efficiency can be improved by inhibition of gibberellin biosynthesis

Abstract: Possibilities to improve maize harvest index and nutrient utilization efficiency by application of plant growth regulators were investigated. In container experiments, the effects of different growth regulators on the development of the maize (Zea mays L.) cultivars Pioneer 3906 and Fabregas were tested. Paclobutrazol (PAC) and chlorocholine chloride (CCC), two inhibitors of gibberellin biosynthesis, as well as gibberellic acid (GA3) were applied at growth stage V5. Three weeks after application of PAC, shoot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 55 publications
(88 reference statements)
1
41
0
Order By: Relevance
“…This good grain yield performance could be due to the shortest ASI with optimal fertilization and least reduction in kernel number (Table 1, Figure 4a). Cultivar Fabregas showed a 9%** decrease in grain yield, which was similar to our previous study, although in this case the difference to the control was not significant (Hütsch & Schubert, 2018).…”
Section: Possible Reasons For Reduced Grain Yield After Pac Treatmentsupporting
confidence: 91%
See 3 more Smart Citations
“…This good grain yield performance could be due to the shortest ASI with optimal fertilization and least reduction in kernel number (Table 1, Figure 4a). Cultivar Fabregas showed a 9%** decrease in grain yield, which was similar to our previous study, although in this case the difference to the control was not significant (Hütsch & Schubert, 2018).…”
Section: Possible Reasons For Reduced Grain Yield After Pac Treatmentsupporting
confidence: 91%
“…Excessive vegetative growth can aggravate water limitations by using too much water before flowering (Passioura & Angus, 2010), as sufficient water availability during the reproductive period is particularly important for yield performance (Yang & Grassini, 2014). The smaller PAC-treated maize plants of our previous study showed a significantly reduced water consumption in comparison with the untreated control (Hütsch & Schubert, 2018). For the cultivar Fabregas, which showed no significant grain yield depression, the water-use efficiency (WUE grain ) was improved by 19% around the time of silking.…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…Compact plants have advantages such as less energy expenditure towards shoot growth, which allows the plant to put in more energy towards flowering, reproduction, and survival 17 . Paclobutrazol has recently been shown to reduce lodging and increase stem strength in maize, along with reducing plant height 18,19 ; low levels of uniconazole application increased abscisic acid and decreased gibberellic acid in both foliar and leaf treatments in maize kernels 20 and reduced plant lodging 21 .…”
Section: Introductionmentioning
confidence: 99%